Low-carbon electricity production through the implementation of photovoltaic panels in rooftops in urban environments: A case study for three cities in Peru - Bazán J. (2018)
Urban environments in Latin America must begin decarbonizing their activities to avoid increasing greenhouse gases (GHGs) emissions rates due to their reliance on fossil fuel-based energy to support economic growth. In this context, cities in Latin America have high potential to convert sunlight into energy. Hence, the main objective of this study was to determine the potential of electricity self-sufficiency production and mitigation of GHG emissions in three medium-sized cities in Peru through the revalorization of underutilized rooftop areas in urban environments.